2010
DOI: 10.1007/s10532-010-9333-4
|View full text |Cite
|
Sign up to set email alerts
|

On the biosorption, by brown seaweed, Lobophora variegata, of Ni(II) from aqueous solutions: equilibrium and thermodynamic studies

Abstract: The biosorption equilibrium isotherms of Ni(II) onto marine brown algae Lobophora variegata, which was chemically-modified by CaCl(2) were studied and modeled. To predict the biosorption isotherms and to determine the characteristic parameters for process design, twenty-three one-, two-, three-, four- and five-parameter isotherm models were applied to experimental data. The interaction among biosorbed molecules is attractive and biosorption is carried out on energetically different sites and is an endothermic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…In general, mechanistic or empirical equations are used to express heavy metal adsorption capacities of different types of biosorbents using batch or column method [ 18 ]. Available literature reports confirm that nearly two dozens of empirical models involving 2, 3, 4, or even 5 parameters have been used to fit batch equilibrium isotherm curves to biosorbents [ 18 , 19 ]. Besides, kinetic models have been described by several authors elsewhere [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, mechanistic or empirical equations are used to express heavy metal adsorption capacities of different types of biosorbents using batch or column method [ 18 ]. Available literature reports confirm that nearly two dozens of empirical models involving 2, 3, 4, or even 5 parameters have been used to fit batch equilibrium isotherm curves to biosorbents [ 18 , 19 ]. Besides, kinetic models have been described by several authors elsewhere [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the decrease in negative DG values with increase in temperature shows that the uptake of Ni(II) by P. ostreatus is favored at lower temperature which is strongly supported by the negative DH value. Basha et al [29] reported similar results for Ni(II) adsorption by Variegata. Moreover, Ho and Ofomaja [24] also reported negative DH value while studying the biosorption of cadmium by coconut copra.…”
Section: Thermodynamic Parametersmentioning
confidence: 58%
“…Some authors have made the incorrect claim that the Frumkin isotherm is only valid for θ < 0.6 [49,50]. The second misconception concerns the use of the Frumkin isotherm and the Fowler-Guggenheim isotherm to fit the same isotherm data [51][52][53][54][55][56][57]. As noted above, the Frumkin isotherm is mathematically analogous to the Fowler-Guggenheim isotherm.…”
Section: Surrogate Qm Based On Freundlich Capacity Parametermentioning
confidence: 99%